2014
DOI: 10.1038/mi.2013.63
|View full text |Cite
|
Sign up to set email alerts
|

Thrombospondin-1 triggers macrophage IL-10 production and promotes resolution of experimental lung injury

Abstract: Mononuclear phagocyte recognition of apoptotic cells triggering suppressive cytokine signaling is a key event in inflammation resolution from injury. Mice deficient in thrombospondin-1 (thbs1−/−), an extracellular matrix glycoprotein that bridges cell-cell interactions, are prone to LPS-induced lung injury and show defective macrophage IL-10 production during the resolution phase of inflammation. Reconstitution of IL-10 rescues thbs1−/− mice from persistent neutrophilic lung inflammation and injury and thbs1−/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
63
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(71 citation statements)
references
References 42 publications
5
63
1
Order By: Relevance
“…However, in vivo studies appear to predominantly support the anti-inflammatory role of CD36. [41][42][43] In particular, reduced CD36 expression in respiratory as well as intestinal mucosa was associated with the development of inflammation. 42,43 In conjunctival epithelial cells, TSP-1:CD36 interaction is reported to activate the immunoregulatory cytokine, TGF-b.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in vivo studies appear to predominantly support the anti-inflammatory role of CD36. [41][42][43] In particular, reduced CD36 expression in respiratory as well as intestinal mucosa was associated with the development of inflammation. 42,43 In conjunctival epithelial cells, TSP-1:CD36 interaction is reported to activate the immunoregulatory cytokine, TGF-b.…”
Section: Discussionmentioning
confidence: 99%
“…9 In addition, our results indicate unaltered TSP-1 expression in EDE conjunctiva with significantly reduced CD36 expression, in contrast to the increased CD36 expression in TSP-1-deficient conjunctiva. Several in vitro studies have reported expression of both proinflammatory 37,38 and antiinflammatory [39][40][41] cytokines in macrophages resulting from the ligation of CD36 by ligands, such as apoptotic cells, oxidized low-density lipoprotein, and TSP-1, but not on epithelial cells. However, in vivo studies appear to predominantly support the anti-inflammatory role of CD36.…”
Section: Discussionmentioning
confidence: 99%
“…Noteworthy transcripts in these categories/pathways included matrix metalloproteinase 25 (MMP25; aka MT-MMP6) (47), thrombospondin 1 (THBS1) (48,49), Toll-like receptor 1 (TLR1) (50, 51), TLR5 (52), chitinase 3-like 1 (CHIL3L1) (53,54), and IL 12b (IL12B) (55,56).…”
Section: Transcriptomic Analysismentioning
confidence: 99%
“…Deficiency of TSP-1 has been reported to show contrasting effects in different experimental studies [26,28,29,58]. Lack of TSP-1 has been reported to promote inflammatory response to retinal injury and inflammatory mediated lung injury in C57BL/6 mice [28,58].…”
Section: Discussionmentioning
confidence: 99%